Preeclampsia-like Syndrome Induced by Severe COVID-19: A Prospective Observational Study. Issue 3 (September 2021) - Mendoza, M.; Garcia-Ruiz, I.; Maiz, N.; Rodo, C.; Garcia-Manau, P.; Serrano, B.; Lopez-Martinez, R.M.; Balcells, J.; Fernandez-Hidalgo, N.; Carreras, E.; Suya, A.
Abstract : ( BJOG . 2020;127:1374–1380) Coronavirus disease 2019 (COVID-19) typically presents as a respiratory infection. Of note, compared with the general pregnant population, increased rates of preeclampsia have been reported in mothers infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Endothelial damage caused by placental oxidative stress leads to the clinical features of preeclampsia including hypertension, proteinuria, elevated levels of liver enzymes, renal dysfunction, thrombocytopenia, and other symptoms. This study aimed to examine the prevalence of clinical, biochemical, and ultrasonographic findings of preeclampsia in women infected with SARS-CoV-2 and also to assess the accuracy in differentiating between actual preeclampsia and preeclampsia-like features associated with COVID-19.